When Does Self-Esteem Relate to Deviant Behavior? The Role of Contingencies of Self-Worth - FERRIS, Donald L. (Institutional Knowledge at Singapore Management University, 2009)
Researchers have assumed that low self-esteem predicts deviance, but empirical results have been mixed. This article draws upon recent theoretical developments regarding contingencies of self-worth to clarify the self-esteem/deviance relation. It was predicted that self-esteem level would relate to deviance only when self-esteem was not contingent on workplace performance. In this manner, contingent self-esteem is a boundary condition for self-consistency/behavioral plasticity theory predictions. Using multisource data collected from 123 employees over 6 months, the authors examined the interaction between level (high/low) and type (contingent/noncontingent) of self-esteem in predicting workplace deviance. Results support the hypothesized moderating effects of contingent self-esteem; implications for self-esteem theories are discussed.